1983
DOI: 10.1002/macp.1983.021840706
|View full text |Cite
|
Sign up to set email alerts
|

Synthèse par voie radicalaire de polymères à extrémités hydroxylées, 12. Etude de la copolymérisation du méthacrylate de méthyle avec divers acrylates et méthacrylates. Détermination des microstructures

Abstract: Methyl methacrylate was copolymerized with butyl or isobutyl acrylates, and butyl, isobutyl, or 2,3-epoxypropyl methacrylates, by hydrogen peroxide, in the presence of ethanol under UV irradiation (at 254 nm) at room temperature. The analysis of the microstructures was based on resonance splitting of the methoxy protons of MMA, depending on their environment. This splitting was not obtained with isobutyl and 2,3-epoxypropyl methacrylates. All the products were found to be predominantly syndiotactic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
12
0
1

Year Published

1986
1986
2006
2006

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 11 publications
1
12
0
1
Order By: Relevance
“…6(a) (F M = 0.17), the methoxy resonance signal of the MMA-centred units has been reinterpreted in terms of five major peak signals, each of which is attributed to an individual or two MMAcentred sequences. This has not been observed before because Brosse et al 15 showed the spectra ofBA-MMA of FM = 0.42 and of higher fractions of MMA in the copolymer. It has been found ( Fig.…”
Section: Resultsmentioning
confidence: 75%
See 3 more Smart Citations
“…6(a) (F M = 0.17), the methoxy resonance signal of the MMA-centred units has been reinterpreted in terms of five major peak signals, each of which is attributed to an individual or two MMAcentred sequences. This has not been observed before because Brosse et al 15 showed the spectra ofBA-MMA of FM = 0.42 and of higher fractions of MMA in the copolymer. It has been found ( Fig.…”
Section: Resultsmentioning
confidence: 75%
“…Expansions of the methoxy region are shown since in particular this region displays additional resonance of the MMA-centred triads as follows: splitting due to combined configurational (= tacticity) and compositional sequence effects. 15 Brosse et aI. 15 published the 100 MHz proton NMR spectra of BA-MMA copolymers and assigned the split methoxy where 0" is O"BM, the coisotacticity parameter (meso configuration between a BA and a MMA unit) and O"MM is the isotacticity (meso configuration between two MMA units).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Copolymer coisotacticity parameter r is not accessible directly, but has been determined with a trial-and-error method [21] from the values of peak X (F X ). The relative intensities of peak X were compared with those calculated theoretically from Equation (1).…”
Section: Resultsmentioning
confidence: 99%